Chapter 4 Norms and Norm Contestation - Orchard, Phil (Taylor & Francis, 2023)
There are growing connections between the IR constructivist focus on norms and norm contestation and Foreign Policy Analysis (FPA). FPA has long had a focus on agency within the state, particularly individual and group-based decision-making. Early constructivist work, by contrast, tended to prioritize agency outside of the state - focusing on norm entrepreneurs and transnational advocacy- and then the state itself in the norm institutionalization process. This led to critiques from FPA scholars that it dismissed human agency. Norms research, however, has evolved. It has moved away from an ontologisation of norms - which focused on structural effects rather than on their socially constructed quality - to examine the importance of norm contestations, practices whereby a diversity of societal agents working across the international/domestic divide seek to contest norm meaning. This leads to a focus on how norms are implemented at the domestic level and creates a closer engagement between constructivism and FPA.